Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12603-015-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of yogurts with vitamin D and calcium enhances the inhibition of serum parathyroid hormone and bone resorption markers: A double blind randomized controlled trial in women over 60 living in a community dwelling home

Abstract: ObjectiveTo evaluate whether fortification of yogurts with vitamin D and calcium exerts an additional lowering effect on serum parathyroid hormone (PTH) and bone resorption markers (BRM) as compared to iso-caloric and iso-protein dairy products in aged white women at risk of fragility fractures.DesignA randomized double-blind controlled trial.SettingA community dwelling home.ParticipantsForty-eight women over 60 years (mean age 73.4).InterventionConsumption during 84 days of two 125 g servings of either vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
1
23
1
1
Order By: Relevance
“…These effects are similar to the active intervention in our study that resulted in a 21% and 14% decrease of PTH and CTX, respectively. A significant decline in PTH and bone resorption markers was also observed after 84 days of vitamin D (400 IU) and calcium-fortified (800 mg) yoghurt consumption twice daily in a community-dwelling population of 57 women aged > 60 years, (mean age 73 years, BMI 30 kg/ m 2 ) living in a sheltered accommodation housing in Hull (England) [24]. Similar effects of calcium and/or vitamin D fortified milk on bone parameters have been observed in Asian populations.…”
Section: Discussionmentioning
confidence: 91%
“…These effects are similar to the active intervention in our study that resulted in a 21% and 14% decrease of PTH and CTX, respectively. A significant decline in PTH and bone resorption markers was also observed after 84 days of vitamin D (400 IU) and calcium-fortified (800 mg) yoghurt consumption twice daily in a community-dwelling population of 57 women aged > 60 years, (mean age 73 years, BMI 30 kg/ m 2 ) living in a sheltered accommodation housing in Hull (England) [24]. Similar effects of calcium and/or vitamin D fortified milk on bone parameters have been observed in Asian populations.…”
Section: Discussionmentioning
confidence: 91%
“…The most common mode of delivery were soups, juices, cereals, desserts, yoghurt, cheese and bread. Mode of delivery varied across the studies, including across the day in 6 studies(Tolbert 2004;Smoliner et al 2008;Grieger and Nowson 2009;Leslie et al 2013;van Til et al 2015;Beelen et al 2017), in breakfast only by 2 studies(Bermejo et al 2008;van Wymelbeke et al 2016), in breakfast and lunch by 1 study(Castellanos et al 2009), in lunch and dinner by 3 studies(Odlund Olin et al 2003;Bonjour et al 2013;Bonjour et al 2015)…”
mentioning
confidence: 99%
“…Given the low vitamin D and calcium intake in many populations, researchers focused on the possibility of fortifying certain products with these nutrients (Whiting et al, 2016). A study carried out on a group of women aged >60 years by Bonjour et al (2015) demonstrated that having two yogurts fortified with calcium (520 mg) and vitamin D (10 µg) a day for three consecutive months significantly increased serum concentration of 25(OH)D and decreased the rate of bone degradation. In a study carried out on postmenopausal women, Bonjour et al (2008) observed that a 6-week period of milk supplementation diminished bone turnover mediated by reduction in parathyroid hormone secretion.…”
Section: Discussionmentioning
confidence: 99%